Factors Associated with Behavior among Normal-Weight and Overweight Adolescent Girls - Yuniar, Rachma Mia (NUTRIZIONE - Nutrition Research and Development Journal, 2024)
Dieting behavior with the specific aim of losing weight is often carried out by adolescent girls who feel dissatisfied with their body shape. Several factors are known to be associated with adolescent girls and their dieting behavior to lose weight. This study aims to determine the factors related to dieting behavior (PD) of normal (N) and overweight (OV) adolescent girls. This is descriptive-analytic with a cross-sectional study design. The samples of this study were 112 adolescent girls in classes X and XI for the 2022/2023 academic year at SMA Islam Sultan Agung 1 Semarang. Data collection using anthropometric measurements and questionnaires. Data analysis using chi-square analysis and Fisher exact test. The results of the study show a relationship between body image (p-value N=0.023; OV=0.047), family influence (p-value N=0.00; OV=0.044), peer influence (p-value N=0.000; OV=0.010), mass media influence (p-value N=0.031; OV=0.006) with the dietary behavior of adolescent girls. It was also found that there was no relationship between knowledge (p-value N=0.059; OV=0.369) and the cultural system that consisting of eating habits (p-value N=0.492; OV=0.640), breakfast habits (p-value N=0.171; OV=0.313), high-calorie snacks intake (p-value N = 0.470; OV = 0.139), and fast food consumption (p-value GN = 0.149; GB = 0.630) with the dietary behavior of adolescent girls. The conclusions of this study are that body image, family influence, peer influence, and mass media influence are related to the dietary behavior of adolescent girls with normal and overweight nutrition status. There is no relationship between knowledge and the cultural system with dietary behavior in normal and overweight adolescent girls.